2011
DOI: 10.1093/hmg/ddr244
|View full text |Cite
|
Sign up to set email alerts
|

Mutational probing of the forkhead domain of the transcription factor FOXL2 provides insights into the pathogenicity of naturally occurring mutations

Abstract: Mutations of the transcription factor FOXL2, involved in cranio-facial and ovarian development, lead to the Blepharophimosis Syndrome. Here, we have systematically replaced the amino acids of the helices of the forkhead domain (FHD) of FOXL2 by glycine residues to assess the impact of such substitutions. A number of mutations lead to protein mislocalization, aggregation and to partial or complete loss of transactivation ability on a series of luciferase reporter systems. To rationalize the results of this glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Beysen et al [13] described a diffuse nuclear distribution of the 104R mutant FOXL2 protein (as for the wild-type) and a normal transcriptional activation. Similar findings were reported for the 104 N and 104G mutants [14,15], involving the same amino acid position. These authors proposed a functional classification of FOXL2 missense mutations, correlating the subcellular localization and aggregation of FOXL2 mutants, transactivation activities and the type of BPES.…”
Section: Discussionsupporting
confidence: 86%
“…Beysen et al [13] described a diffuse nuclear distribution of the 104R mutant FOXL2 protein (as for the wild-type) and a normal transcriptional activation. Similar findings were reported for the 104 N and 104G mutants [14,15], involving the same amino acid position. These authors proposed a functional classification of FOXL2 missense mutations, correlating the subcellular localization and aggregation of FOXL2 mutants, transactivation activities and the type of BPES.…”
Section: Discussionsupporting
confidence: 86%
“…A clear correlation was found between the transcriptional activity of FOXL2 mutations on two different reporter promoters and the BPES type [25]. In a very recent study by Todeschini et al [26], the amino acids of the helices of the forkhead domain of FOXL2 were systematically replaced by glycine residues to assess the impact of these artificial mutations. A number of mutations led to protein mislocalization, aggregation and to partial or complete loss of transactivation ability on a dozen of luciferase reporter systems.…”
Section: Foxl2 Impairment In Bpesmentioning
confidence: 99%
“…Extrapolation of this analysis to natural mutations was in agreement with the findings obtained for the artificial mutations. This study brought important insights into the molecular effects of FOXL2 missense mutations located in the forkhead domain, and provided an apparently reliable in silico predictive tool for their phenotypic effects [26]. …”
Section: Foxl2 Impairment In Bpesmentioning
confidence: 99%
“…In humans, FOXL2 heterozygous mutations are responsible for the blepharophimosis-ptosis-epicanthus inversus syndrome (BPES), characterized by facial malformations often associated with primary ovarian insufficiency (POI) (Crisponi et al, 2001). Recent works have shown that FOXL2 mutations impairing its DNA binding and/or transcriptional activity are responsible for POI occurrence in BPES (Dipietromaria et al, 2009; Todeschini et al, 2011). Interestingly, a specific somatic mutation of FOXL2 has been identified in more than 95% of adult-type granulosa cell tumors (GCTs) confirming the strong association of FOXL2 with granulosa cell fate and function (Shah et al, 2009; Jamieson and Fuller, 2012).…”
Section: Introductionmentioning
confidence: 99%